Social trust and subjective well-being of first-generation college students in China: the multiple mediation effects of self-compassion and social empathy - Wang, Qun; Zhi, Kuiyun; Yu, Baohua; Cheng, Jun (Frontiers in Psychology, 2023)
Previous studies have found that subjective well-being is associated with social trust, self-compassion, and social empathy. Based on online fieldwork with 662 first-generation college students (54.7% male) in China, this study aimed to investigate the serial mediation effects of self-compassion and social empathy on the relationship between social trust and subjective well-being. The results showed that subjective well-being was significantly positively correlated with social trust, trust in people, self-compassion, and social empathy. Both self-compassion and social empathy partially mediated the relationship between social trust and subjective well-being, and fully mediated the association between trust in people and subjective well-being. We used a serial mediation model to estimate the effect of general social trust, including trust in people, on subjective well-being. The findings that self-compassion and social empathy mediated the relationship between trusting attitudes toward society, especially people, and subjective well-being expand the literature on social trust and the mechanism of social trust on subjective well-being. The results also highlight the significance of improving mental health education and intervention among first-generation college students in China.